The Influence of Destination Image, Food and Beverage Quality, and Prices on Purchasing Decisions at the Surabaya Culinary Tourism Center - Iradawati, Sofiah Nur (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
The Surabaya Culinary Tourism Center (SWK) plays a vital role in developing Micro, Small and Medium Enterprises (MSMEs) by providing opportunities for MSMEs to market their products. This research investigates the influence of destination image, food and beverage quality, and price on purchasing decisions at SWK Surabaya. Quantitative methods were used with a Likert Scale to measure respondents' attitudes. Data was analysed using Structural Equation Modeling Partial Least Square (SEM-PLS). The research results show that destination image and price significantly influence purchasing decisions, while food and beverage quality has a positive but not significant influence. The implication of this research is the importance of improving destination image and pricing strategies to increase the attractiveness of SWK Surabaya